The acidic microenvironment promotes pancreatic cancer progression via the lncRNA-LOC100507424/E2F1/FOXM1 axis - Deyang Mu; Ying Shi; Runxuan Sun; Bing Han; Kai Zhong; Yilu Ye; Jungang Zhang (BMC Cancer)
Abstract Pancreatic cancer is highly aggressive and sensitive to acidic microenvironments, which promote cancer cell survival and invasion. Long non-coding RNAs (lncRNAs) play crucial roles in cancer biology, helping cells adapt to microenvironmental changes, but their functions in the acidic microenvironment of pancreatic cancer are understudied. This study investigated the role of lncRNA LOC100507424 in pancreatic cancer, previously linked to glioma stem cells. Clinical specimens and cell line models cultured under acidic conditions showed that LOC100507424 was upregulated in pancreatic cancer tissues and further increased in acidic environments. Functional assays demonstrated that knockdown of LOC100507424 inhibited cell proliferation, invasion and metastasis. Mechanistically, LOC100507424 transcriptionally regulated FOXM1 expression through its interaction with E2F1. In vivo studies confirmed that LOC100507424 promoted tumor growth in nude mice. These findings highlight the significance of lncRNAs in the acidic microenvironment of pancreatic cancer and suggest potential therapeutic targets.